PENGEMBANGAN SISTEM PEMBELAJARAN DIGITAL BERBASIS HOTS - Husna, Asmaul; Masitoh, Cahya; Lestari, Etika; Ananda, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the development of digital learning systems based on Higher Order Thinking Skills (HOTS) to enhance the quality of 21st-century education. The rapid advancement of digital technology necessitates a pedagogical transformation that shifts focus from mere content mastery to the cultivation of critical thinking, creativity, collaboration, and complex problem-solving skills. Using a library research method, this study examines various scholarly journals, scientific articles, and relevant literature concerning digital learning and HOTS. The findings suggest that the integration of digital technology into the learning process significantly increases student engagement, strengthens analytical and evaluative capabilities, and fosters student creativity through interactive media, digital platforms, and project-based learning models. Furthermore, a HOTS-based digital learning system provides instructional flexibility and supports more innovative and contextual learning environments. However, implementation still faces substantial challenges, such as infrastructure limitations and gaps in educators' digital competencies. Consequently, strategic support for facilities, comprehensive teacher training, and sustainable development of instructional media are essential to ensure the effective implementation of HOTS-based digital learning in improving educational standards.